Utilizing Artistic Expressions Inspired by the Equipment of the Audio-Visual Department to Develop the Drawings of Female Students at the Institute of Fine Arts (The International Journal for Scientific Research, 2024)
Our current research (The Employment of Artistic Expressions Inspired by Audiovisual Equipment to Develop the Drawings of Female Students at the Institute of Fine Arts) is divided into three chapters. Due to the importance of the topic, the problem was formulated through the following questions: To what extent do female students in the Audiovisual Department benefit from artistic expressions inspired by their specialization in developing their drawings? Additionally, to what extent does the subject of planning and colors contribute to improving the students' level and graduating them as art education teachers? The current study aims to reveal the impact of employing artistic expressions inspired by audiovisual equipment on the development of students' drawings and their artistic performance. The current study used a descriptive analytical approach in the research procedures and resulted in a set of findings that included the concept of work as being either realistic or expressive, as well as the artistic expressions and tools. The artistic expressions were represented by direct relationships influenced by the tools and equipment of the Audiovisual Department, as well as indirect relationships with the tools of the Audiovisual Department, but with a clear expressive significance. The results also addressed the development of students' drawings through form and content, which was generally verified in models (1, 2, 3, 4). As for color, the color ability used to express the idea and depict scenes was achieved according to each individual's expression. Regarding the diversity of equipment, the diversity in drawing the equipment was realized, and the results touched on the color values of the selected models.
Keywords: Employment; Artistic Expressions; Equipment; Audio Department; Development